Intertidal Mediterranean Coralline Algae Habitat Is Expecting a Shift Toward a Reduced Growth and a Simplified Associated Fauna Under Climate Change - Marchini, Agnese; Ragazzola, Federica; Vasapollo, Claudio; Castelli, Alberto; Cerrati, Gabriella; Gazzola, Federica; Jiang, Chulin; Langeneck, Joachim; Manauzzi, Maria Chiara; Musco, Luigi; Nannini, Matteo; Zekonyte, Jurgita; et al. (Frontiers in Marine Science, 2019)
Coralline algae represent the most important bioconstructors in the Mediterranean Sea and are currently impaired by the effects of climate change (CC), particularly by global warming (GW) and ocean acidification (OA). We studied the effects of these two drivers on Ellisolandia elongata, an intertidal coralline algae that is known to host a rich biodiversity of associated fauna. We cultured turfs of E. elongata in experimental conditions of increased temperature and OA (using the values of the IPCC scenario RCP- 8.5 expected for 2100: actual mean temperature +3 °C and pH=7.78), and estimated alteration of algal linear growth and community structure, focusing especially on peracarid crustaceans and annelids. Our findings revealed a decrease in linear growth, yet with no significant changes on structural integrity, and a simplification of associated community, in particular for peracarids. Our study contributes to understand community-level response to CC drivers, highlighting the vulnerability of the fauna associated to an important Mediterranean marine habitat.